Prevalence and Factors Associated with Anemia among Pregnant Women at Birat Medical College Teaching Hospital - Deo, Amit; Pradhan, Tarun (Birat Journal of Health Sciences, 2022)
Introduction: Anemia in pregnancy is associated with many adverse fetal and maternal outcomes. It is the commonest hematological disorder that occurs in pregnancy. Prevalence of anemia in pregnant women is very high worldwide, especially in developing countries. The objective of this study was to find the prevalence and the factors associated with anemia among pregnant women attending Birat Medical College Teaching Hospital. Methodology: A Quantitative, cross-sectional study conducted for 6 months in the Department of Obstetrics and Gynaecology OPD at Birat Medical College Teaching Hospital. All consecutive pregnant women attending for antenatal checkup in the department of Obstetrics and Gynaecology OPD at Birat Medical College Teaching Hospital were included in the study. Participants with multiple pregnancy, history of recent blood transfusion, chronic kidney disease and other chronic medical diseases were excluded from the study. All participants were advised for Hemoglobin level checkup at first ANC visit as a routine antenatal investigation and questionnaire was asked about the associated risk factors of anemia on predesigned proforma. The collected data was entered in Microsoft Excel and analyzed by using SPSS version 22. Results: The prevalence of anemia was high (58.9%)of which mild anemia (Hb level 9-10.9 gm/dl) was found in 56.1% of participants, moderate anemia (Hb level 7-8.9 gm/dl) found in 2.1% of participants and severe anemia (Hb level <7 gm/dl ) was found in 0.8 % of participants. Factors statistically associated with anemia in pregnancy were caste, literacy, vegetarian diet of pregnant women. Conclusion: The prevalence of anemia was found to be very high in pregnancy. Anemia in pregnancy was found to be associated with literacy, socioeconomic status and dietary habits of pregnant women.